Malacca and Ming Dynasty in 15th-16th Centuries: A Diplomatic Relations and Regional Stability - Darmawan, Budi; Erasiah, Erasiah; Hakim, Lukmanul (JUSPI (Jurnal Sejarah Peradaban Islam), 2024)
This study investigates the intricate relationship in diplomacy of Malacca with the Ming Dynasty of China during the 15th century in the Malacca Strait, with a focus on its impact on Diplomatic Relations. Employing a comprehensive historical methodology, including heuristic exploration, critical examination of sources, data interpretation, and historiographical analysis, the research reveals the significant consequences of mutually beneficial diplomatic engagements and trade interactions the bond from two region China and Malacca. When faced with threats came from Majapahit and Siam, Malacca found assistance from China (Ming Dynasty), resulting in the formation of a robust alliance. This diplomatic collaboration commenced with the arrival of Chinese delegated Yin C'ing in 1403 AD and was further reinforced by the influential visit of Cheng Ho in 1409 AD, solidifying the relationship between them. This mutually beneficial relationship not only safeguarded Malacca and elevated its trading stature but also facilitated China's access to valuable spices, while providing military protection from the Ming Dynasty. The deep relations Malacca had with China during the 15th century shows how their strengthened political association, connections and security also helps their cultural interactions.